Association of cardiac care regionalization with access, treatment, and mortality among patients with ST-elevation myocardial infarction - Shen, Yu-Chu (Circ Cardiovasc Qual Outcomes, 2021)
BACKGROUND: Regionalization of ST-elevation myocardial infarction (STEMI) systems of care has been championed over the past decade. While timely access to PCI has been shown to improve outcomes, no studies have determined how regionalization has affected the care and outcomes of patients. We sought to determine if STEMI regionalization is associated with changes in access, treatment, and outcomes. METHODS: Using a difference-in-differences approach, we analyzed a statewide, administrative database of 139,494 patients with STEMI in California from 2006-2015 using regionalization data based on a survey of all local Emergency Medical Services agencies in the state. RESULTS: For patients with STEMI, the base rate of admission to a hospital with PCI capability was 72.7%, and regionalization was associated with an increase of 5.34 percentage points (95% CI 1.58 to 9.10), representing a 7.1% increase. Regionalization was also associated with a statistically significant increase of 3.54 (95% CI 0.61 to 6.48) percentage points in the probability of same-day PCI, representing an increase of 7.1% from the 49.7% base rate, and a 4.6% relative increase (2.97 percentage points; 95% CI 0.1, 5.85) in the probability of receiving PCI at any time during the hospitalization. There was a 1.84 percentage point decrease (95% CI −3.31, −0.37) in the probability of receiving fibrinolytics. For 7-day mortality, regionalization was associated with a 0.53 (95% CI −1 to −0.06) percentage point greater reduction (representing 5.8% off the base rate of 9.1%) and a 1.75 percentage point decrease in the likelihood of all-cause 30-day readmission (95% CI −3.39 to −0.11; representing 6.4% off the base rate of 27.4%). No differences were found in longer-term mortality. CONCLUSIONS: Among patients with STEMI in California from 2006 to 2015, STEMI regionalization was associated with increased access to a PCI-capable hospital, greater use of PCI, lower 7-day mortality, and lower 30-day readmissions.